A novel impedance source fed H-type flying capacitor multilevel inverter - Chinnapettai Ramalingam Balamurugan; P. Vijayakumar; T. Sengolrajan (Institute of Advanced Engineering and Science, 2019)
In this paper, simulation using MATLAB/SIMULINK is performed withbipolar triangular fixed amplitude multi-carrier Phase Disposition (PD)PWM strategy with sine wave, Third Harmonic Injection, 60 degree Pulse Width Modulation and stepped wave reference for the chosen impedance Source based H-Type flying capacitor Multilevel Inverter (ISBH-Type FCMLI). The root means square value of the fundamental component and Total Harmonic Distortion of the output voltage which are the most important performance indices for the chosen inverter topologies are evaluated presented and compared for various references through duty ratios. From the simulation results it is observed that for various references the THD is almost similar but the root mean square value in terms of voltage is more for THI, 60 degree PWM and stepped wave reference with phase disposition strategy. The results are obtained for ma (amplitude modulation index) < 1 (under amplitude modulation index), ma=1 (normal amplitude modulation index) and ma > 1 (over amplitude modulation index).